Microglia-mediated neuron death requires TNF and is exacerbated by mutant Huntingtin - Alexander P. Young; Eileen M. Denovan-Wright (Elsevier, 2024)
Microglia, the resident immune cells of the brain, regulate the balance of inflammation in the central nervous system under healthy and pathogenic conditions. Huntington's disease (HD) is a chronic neurodegenerative disease characterized by activated microglia and elevated concentrations of pro-inflammatory cytokines within the brain. Chronic hyperactivation of microglia is associated with brain pathology and eventual neuron death. However, it is unclear which specific cytokines are required for neuron death and whether HD neurons may be hypersensitive to neuroinflammation. We assessed the profile of microglia-secreted proteins in response to LPS and IFNγ, and a conditioned media paradigm was used to examine the effects of these secreted proteins on cultured neuronal cells. STHdhQ7/Q7 and STHdhQ111/Q111 neuronal cells were used to model wild-type and HD neurons, respectively. We determined that STHdhQ111/Q111 cells were hypersensitive to pro-inflammatory factors secreted by microglia, and that TNF was required to induce neuronal death. Microglia-mediated neuronal death could be effectively halted through the use of JAK-STAT or TNF inhibitors which supported the requirement for TNF as well as IFNγ in the process of secondary neurotoxicity. Further data derived from human HD patients as well as HD mice were suggestive of enhanced receptor density for TNF (TNFR1) and IFNγ (IFNGR) which could sensitize the HD brain to these cytokines. This highlights several potential mechanisms by which microglia may induce neuronal death and suggests that these mechanisms may be upregulated in the brain of HD patients.